Correction: Calcium-Activated-Calcineurin Reduces the In Vitro and In Vivo Sensitivity of Fluconazole to Candida albicans via Rta2p. - Yu Jia; Ren-Jie Tang; Lin Wang; Xiang Zhang; Ying Wang; Xin-Ming Jia; Yuan-Ying Jiang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0048369.].